3D cold pressure welded components – From the bonding mechanisms to the production of high strength joints. Issue 8 (25th July 2019) - Gerlitzky, C.; Kuhn, C.; Groche, P.; Tran, T.H.; Zhang, S.; Peter, N.J.; Rohwerder, M.
Abstract: In this work, a comprehensive analysis of the bonding mechanism involved in the formation of highly stable cold pressure welded aluminum‐steel components is presented. After identification of relevant process steps to realize bonding the process is modified. Focusing on surface preparation methods, systematic manipulations are employed to identify the relevant parameters promoting the bond formation. The analysis is carried out by tensile stress testing of micro and macro samples as well as high resolution imaging of the joint zone. The results are enables in a deeper understanding of the bonding mechanism. Translation abstract: In dieser Arbeit wird eine umfassende Analyse des Bindungsmechanismus, der an der Bildung von hochstabilen, kaltpressgeschweißten Aluminium‐Stahl‐Verbindungen beteiligt ist, vorgestellt. Nach dem Identifizieren relevanter Prozessschritte zur Realisierung eines Verbunds wird der Prozess modifiziert. Die Schwerpunkte der Untersuchungen liegen auf den Oberflächenpräparationsmethoden. Durch systematische Veränderungen werden die relevanten Parameter zur Ausbildung der Bindung identifiziert. Die Analyse erfolgt durch Zugspannungsprüfungen an Mikro‐ und Makroproben sowie durch hochauflösende Aufnahmen der Fügezone. Die Ergebnisse führen zu einem tieferen Verständnis des Bindungsmechanismus.